The effect of financial development on energy consumption in the case of Kazakhstan - Shahriyar Mukhtarov; Sugra Humbatova; Ilgar Seyfullayev; Yashar Kalbiyev (Journal of Applied Economics, 2020)
This study investigates the relationship between energy consumption, financial development, economic growth, and energy prices in Kazakhstan, utilizing VECM technique to the data spanning from 1993 to 2014. Estimation results reveal that there is a positive and statistically significant impact of financial development and economic growth on the energy consumption while, energy prices proxied by CPI has a negative effect on energy consumption in the long run for the Kazakhstani case which are in line with the expectations and with the theoretical findings. This finding also shows that a 1% increase in financial development and economic growth increases energy consumption by 0.11 and 0.39%, respectively.
Keywords: 330; VECM; Energy consumption; financial development; Kazakhstan